Investigating the effect of ambient temperature, sound type, and noise level on the heart rate of the elderly - Mohammad Tohidi; Karen Fatahi; Maryam Beigi (Experimental Gerontology, 2025)
Background: Given the increasing elderly population in the future, attention to the health of older adults is important. Environmental factors, including ambient temperature, sound type, and noise level, greatly affect the health of older adults. This study looks at how these elements influence the heart rate of elderly individuals. Method: This study involves laboratory research with 216 elderly male participants from Ilam province in Iran over four months, from May to August 2024. Participants were exposed to different ambient temperature settings (20 °C, 25 °C, and 30 °C) and four noise levels (55, 65, 75, and 85 dB(A)) using sound types like music, traffic, and crowded noise. They were randomly divided into three equal groups of 72 by ambient temperature and then into subgroups of 24 based on the three sound type; finally, these subgroups were tested under four different noise levels, with each group consisting of 6 participants. The data from participants were analyzed using a three-way ANOVA model. Results: The findings showed that ambient temperature, sound type, and noise level greatly affected older adults' heart rate, with strong statistical significance. There was a notable interaction between ambient temperature and noise level. However, other interactions did not show significant relationships with heart rate. Conclusion: The study highlights important impacts on the health of elderly in noisy urban areas. It shows that long exposure to high noise and heat increases heart rate. This research emphasizes noise control and heat management to protect older adults and informs public health policies and urban planning.